2. Anti-Bacterial Activity Of N-Hexane Extract Of Malacca Leave (Phyllanthus emblica) On Mice (Mus musculus) Inoculated By Staphylococcus epidermidis In Vivo - Nada Sarah Syahputri; Nuzul Asmilia; Rinidar Rinidar; Amalia Sutriana; Fakhrurrazi Fakhrurrazi; Ginta Riady (Jurnal Medika Veterinaria, 2021)
Malacca plant (Phyllanthus emblica) is one of the medicinal plants. The purpose of this study was to determine the effect of n-hexane extract of Malacca (Phyllanthus emblica) leaves on the growth of Staphylococcus epidermidis bacteria in vivo. All mice were first induced by Staphylococcus epidermidis bacteria. Negative control (K1) was given aquadest, positive control (K2) was given ciproflaxacin suspension at doses of 20 mg/kg BW, while K3, K4, and K5 were given n-hexane extract of Malacca leave at dose of 100 mg/kg BW, 200 mg/kg BW, and 300 mg/kg BW. Respectively blood sampling was carried out on the 5th day after treatment. Data were analyzed using one-way analysis of variance (ANOVA). The results showed that the mean (± SD) number of bacterial colonies in K1 was 656x10² cfu/ml. The average number of bacterial colonies in K2 was 2328x10² cfu/ml. The average number of bacterial colonies given n-hexane extract of malacca leave 100 mg/kg BW on K3 was 359,60x10² cfu/ml. The average number of bacterial colonies given n-hexane extract of malacca leave 200 mg/kg BW at K4 was 200x10² cfu/ml and the average number of bacterial colonies given n-hexane extract of malacca leave 300 mg/kg BW at K5 was 3483x10² cfu/ml. The results showed there were no significant difference among treatment groups (P 0.05). N-hexane extract of malacca leave was unable to inhibit the growth of Staphylococcus epidermidis bacteria in vivo